If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = -13 + -1x Solving 5 = -13 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 5 + x = -13 + -1x + x Combine like terms: -1x + x = 0 5 + x = -13 + 0 5 + x = -13 Add '-5' to each side of the equation. 5 + -5 + x = -13 + -5 Combine like terms: 5 + -5 = 0 0 + x = -13 + -5 x = -13 + -5 Combine like terms: -13 + -5 = -18 x = -18 Simplifying x = -18
| x+9=-7 | | 8x=1500 | | (2-x)(3+x)=2(3-2x)(2-x) | | 5y+7=9+7y | | 18x=1500 | | 250x=1500 | | 583-3h=1667 | | 7x-9-x+3=0 | | 6x-7+9=3x | | 3+2(x-1)=-1 | | -3.8x=10.83 | | 10-4x=6x-5 | | 7x+x+100=1700 | | -2x+16=3x-44 | | -2x-26=62 | | 9v+9-3r=6v+2-8 | | 9x-5.62=-3.73 | | 36a^2+9ab-10b^2=0 | | 113+3h=1250 | | y=1.5x^2+6x+10 | | 12-9x=2x-21 | | 9a-4=2(3a+4) | | 30-x^2=0 | | 9y+1=45-2y | | 12-9x=2x-12 | | 18x^3-39x^2-24x=0 | | 8x+5+7+2x= | | 4(5-x)+6x=8 | | 5-3(2-x)=29 | | 6(x-3)-2(7-x)=8 | | 4x^2=225 | | 2y+8+5y+1= |